The relationship between figureheads and managerial leaders in the private university sector: a decentralised, competency-based leadership model for sustainable higher education - Alam, Gazi Mahabubul (Multidisciplinary Digital Publishing Institute, 2022)
Using school management settings, important substantial leadership models (such as “instructional”, “constructive”, and “distributed”) are developed. University leadership, especially in the private sector, is an understudied topic. While private universities need to generate revenue for profits and survival, they should at the same time retain a sound education philosophy—an extremely difficult task. Studies are yet to be conducted to understand how leaders of private universities handle this challenge, and this issue motivates the present study. Using Bangladesh as a case study, this qualitative analysis discovers that the “visionary” leadership approach is mainly used for the business management models that governs private-sector universities. This does not allow an established education leadership model to function well, if at all. This has seriously challenged education philosophy. Innovation of a specialised private-sector university leadership model is therefore required. A “distributed leadership” approach is the latest innovation for educational leadership, which is mainly applicable for the public system, especially for K12 provision. Considering a distinct operational norm of the private university sector in a developing nation, this research suggests a dynamic revenue-collection model which would enable the development of a decentralised, competency-based leadership approach. While the private university sector may not be able to implement “distributed leadership” model given the operational differences and challenges involved, the proposed model may support the private university sector to function in tertiary level, as the “distributed model” functions for K12 provision. This proposed model (decentralised, competency-based leadership) would further be able to ensure a specialised operational directive for private universities in an emerging nation that may ensure a distinctive nature for the sector’s delivery of sustainable higher education (HE) without compromising the philosophy and role of HE.